2018
DOI: 10.1016/j.ejvs.2018.01.026
|View full text |Cite
|
Sign up to set email alerts
|

Structured Reporting of CT Angiography Runoff Examinations of the Lower Extremities

Abstract: Referring clinicians perceive SRs of CTA runoff examinations of the lower extremities as offering superior clarity, completeness, clinical relevance, and usefulness than CRs. Structured reporting does not appear to alter further testing or therapy in patients with known or suspected peripheral arterial disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
10
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 23 publications
7
10
0
Order By: Relevance
“…These results are in line with previous studies that were able to demonstrate a correlation between structured reporting and high report quality in various diagnostic modalities [21, 2325, 29, 36]. Our results also show that inexperienced examiners highly prefer SRs.…”
Section: Discussionsupporting
confidence: 93%
“…These results are in line with previous studies that were able to demonstrate a correlation between structured reporting and high report quality in various diagnostic modalities [21, 2325, 29, 36]. Our results also show that inexperienced examiners highly prefer SRs.…”
Section: Discussionsupporting
confidence: 93%
“…Overall analysis of user satisfaction showed a clear superiority of structured reporting. These results are consistent with previous publications that were able to correlate the use of structured reporting with superior report quality for a wide range of diagnostic modalities [24,[26][27][28][29]31,32,34,36].…”
Section: Discussionsupporting
confidence: 92%
“…To the best of our knowledge there have been no previous prospective studies on SRs of head and neck ultrasound examinations. Additionally, this has been one of the largest prospective studies on structured reporting in general [1013, 33, 34]. Our data showed that the use of SRs leads to significantly improved report quality, completeness and readability.…”
Section: Discussionmentioning
confidence: 54%